2003
DOI: 10.1034/j.1600-0854.2003.00088.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Complex Glycosylation Increases the Formation of PrPsc

Abstract: N-linked glycans with complex structure have a major role in the biological activity of a wide variety of cell surface and secreted glycoproteins. Here, we show that geldanamycin, an inhibitor of Hsp90, interferes with the formation of complex glycosylated mammalian prion protein (PrP C ). Similarly to inhibitors of a-mannosidases, geldanamycin stabilized a high mannose PrP C glycoform and prevented the subsequent processing into complex structures. Moreover, a PrP/Grp94 complex could be isolated from geldanam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
58
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(63 citation statements)
references
References 52 publications
5
58
0
Order By: Relevance
“…However, Korth et al (17) and later Neuendorf et al (22) detected unglycosylated PrP on the cell surface of different cell lines when transfected with some but not all glycosylation mutants, suggesting that the mutation of an amino acid rather than the lack of sugars can influence the intracellular fate of PrP. However, it has been also observed that PrP without complex-type glycans after treatment with geldanamycin localizes to the cell surface despite any alteration in Prnp (19), suggesting that PrP can traffic independently of the presence of mature sugars or different amino acids. Our results show that the presence of just one sugar chain is sufficient for the protein to leave the intracellular compartments of the endoplasmic reticulum and Golgi apparatus and traffic to the cell surface.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…However, Korth et al (17) and later Neuendorf et al (22) detected unglycosylated PrP on the cell surface of different cell lines when transfected with some but not all glycosylation mutants, suggesting that the mutation of an amino acid rather than the lack of sugars can influence the intracellular fate of PrP. However, it has been also observed that PrP without complex-type glycans after treatment with geldanamycin localizes to the cell surface despite any alteration in Prnp (19), suggesting that PrP can traffic independently of the presence of mature sugars or different amino acids. Our results show that the presence of just one sugar chain is sufficient for the protein to leave the intracellular compartments of the endoplasmic reticulum and Golgi apparatus and traffic to the cell surface.…”
Section: Discussionmentioning
confidence: 94%
“…PrP overexpression represents a major problem, because it is now clear that different results may be obtained when PrP expression levels are altered in both cell cultures and transgenic mice (23,52). Some experiments performed in cell culture models have shown that the lack of carbohydrates can in some way destabilize PrP C structure, thus allowing it to acquire all of the PrP hallmarks (16,17,19). However, recently, Neuendorf et al (22) have shown that altered glycosylated PrPs display just some of the pathogenic protein characteristics, such as detergent insolubility, while maintaining the PK sensitivity of wild type PrP.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the fully matured protein both N-glycosylation sites are occupied and typically four variants of prion protein co-exist: the double-glycosylated, two mono-glycosylated and the unglycosylated. It has been reported that lack of sugars would induce the transition of PrP C to PrP Sc in vitro, suggesting that the modification in glycosylation may contribute to the development of the disease (8). We thus investigated the correlation of apoptosis and glycosylations of PrP Sc in the brain tissues of the hamsters infected with scrapie stain 263K (9).…”
Section: Introductionmentioning
confidence: 99%